New insights into the Ar-matrix-isolation FTIR spectroscopy and photochemistry of dichloroacetyl chloride, ClC(O)CHCl2: Influence of O2 and comparison with gas-phase photochemistry - Tamone, Luciana Mariel (2021)
Photolysis products of dichloroacetyl chloride (DCAC) isolated in Ar matrix and in gas phase, in the absence and presence of molecular oxygen, were studied by means of FTIR spectroscopy. The samples were exposed to light of different energy ranges (200-800, 280-320, 350-450 and 400-800 nm). DCAC is photostable when irradiated with light of wavelengths above 400 nm, and gives dichloroketene after photolysis with light between 280-320 and 350-450 nm. Exposure of DCAC to broad-band radiation (200-800 nm) produces dichloroketene as an intermediate photoproduct, and different 1:1 CHCl3:CO molecular complexes after further irradiation. HCl, CO and CHCl3 were detected in gas-phase DCAC photolysis. ClC(O)CCl2CCl2H molecule was also proposed, in a mechanism that involve the insertion of :CCl2 biradical into the CC bond of DCAC. The photochemical reaction of DCAC with O2 in Ar matrix gives Cl2CO and CO2. The same photoproducts, together with HCl, were observed in the gas-phase photochemical reaction. Additionally, the FTIR spectra of DCAC isolated in solid Ar were fully interpreted in terms of an equilibrium between syn (the HC bond syn with respect to the CO bond) and gauche conformers. Some absorptions, which grow as the DCAC:Ar ratio increases, were attributed to dimeric forms. The most stable dimer was predicted by DFT calculations as composed by two DCAC molecules with syn conformations, interacting through two H-bonds in a structure with Ci symmetry.